EPISTEMIC STATUS OF ARTIFICIAL INTELLIGENCE IN ISLAMIC LAW: ANALYSIS OF THE POSSIBILITY OF NEW SOURCES OF KNOWLEDGE IN THE DIGITAL AGE - Nuriaman, Nuraiman; Muh Faturrahman; Kurniati, Kurniati (Wasīlah: Journal Of Sharia Sciences, 2026)
The development of artificial intelligence has brought about significant changes in the way humans acquire and manage knowledge, including in the religious sphere such as the provision of fatwas and Islamic legal references. This phenomenon has sparked debate not only regarding the normative aspects of its use, but also regarding the epistemic status of knowledge produced by artificial intelligence within the framework of Islamic epistemology. This study aims to understand the mechanisms of knowledge formation in artificial intelligence, examine the concepts of revelation and reason as sources of knowledge in the tradition of Islamic philosophy, and determine the epistemic position of artificial intelligence in relation to revelation and reason. This research is a literature study with an analytical-conceptual nature and a philosophical-normative approach, using conceptual analysis techniques on literature on Islamic philosophy, epistemology, and artificial intelligence studies. The results of the study show that artificial intelligence knowledge is representational and derivative because it is entirely dependent on human-made data and algorithms. Artificial intelligence cannot be positioned as a source of knowledge in Islamic epistemology because it does not fulfill the characteristics of revelation or reason. However, artificial intelligence can be placed as an instrument of reason that assists the process of Islamic legal reasoning as long as it remains under the authority of revelation, human reason, and the objectives of Sharia